Development of Social Emotional Based Book Activity: Product Validity - Dwijayanti, Ida; Andri Nugroho, Aryo; Esti Utami, Rizky; Khasanah, Ismatul (KnE Social Sciences, 2024)
Indonesia is in the fifth highest position out of 78 countries where most of the students experience bullying. The Ministry of Education and Culture has issued various policies intended to overcome this problem, one of which is establishing the Pancasila student profile as the vision of Indonesian education. To support this, educators are needed who have high qualifications, competence, and dedication in carrying out their professional duties. Based on extracting information from preliminary research that has been carried out by researchers, the main problem faced by early childhood teachers is the lack of references regarding activities that can be carried out by early childhood teachers to realize the themes set by the Ministry in realizing an integrated Pancasila student profile, teaching media, and evaluation tools. This research aims to produce an activity book for teachers based on social emotional learning, which has been proven to be practical and effective in increasing the competency of early childhood postal teachers, and to produce an activity book for students based on social emotional learning which has an impact on the growth and development of Pancasila student profiles for PAUD students. The data collection and analysis methods used in the first year were documentation methods to obtain data on teaching materials before they were developed, questionnaires to obtain expert validation data, and readability by partner teachers. All data will be analyzed descriptively. Keywords: teacher activity book, student activity book, teacher competencies, Pancasila student profile